An Exploration of CSR and Employee Engagement in MNCs operating in Pakistan - Asim, Farah (Curtin University, 2019)
CSR has become a popular subject of public debate and organizational success over the years. Using stakeholder theory this study explores CSR and employee engagement in MNCs operating in Pakistan by adopting qualitative collective case study approach. Data is collected via organizations documents and semi-structured interviews with HRM&D managers and employees. Findings from this study is expected to offer insights into the link between CSR and HRM strategies for enhanced employee engagement in today’s diverse workplace.